Penerapan Pendekatan Teknis untuk Meningkatkan Gerak Dasar Manipulatif dalam Pembelajaran Fielding Games Sederhana - Jayanti, Ayu Dwi; Suntoda, Andi; Budiman, Didin (TEGAR: Journal of Teaching Physical Education in Elementary School, 2019)
This study was aimed to determine the increase of students’ manipulative movement skills through the implementation of simple learning class games on fourth grade elementary achool students. The research method of this study was classroom action research. The data analysis by reducing data and describing data in table form, so that  the average value and percentage of completeness of learning could be found. The subjects of this study were fourth grade students in elementary school student in Bandung. The total of the students were 33 students, which consisted of 17 male students and 16 female students. The results of the study in the first cycle showed that the manipulative movement skillsof students achieved (63.88%), while in the second cycle showed that the manipulative movement skills  increased to reach (80.55%). This research show that the use of  a technical approach can improve manipulative movement skills through simple field games lessons. AbstrakPenelitian ini bertujuan untuk mengetahui peningkatan gerak dasar manipulatif melalui penerapan pembelajaran field games sederhana kelas 4 sekolah dasar. Penelitian ini menggunakan metode penelitian tindakan kelas. Analisa data dilakukan dengan mereduksi data dan memaparkan data dalam bentuk tabel, sehingga dapat dicari nila rata-rata dan persentase ketuntasan belajar. Subjek dalam penelitian ini adalah siswa kelas IV Sekolah Dasar di Kota Bandung yang berjumlah 33 siswa. Terdiri dari 17 orang siswa putra dan 16 orang siswa putri. Hasil penelitian pada siklus I menunjukkan gerak dasar manipulatif siswa mencapai hasil (63,88%), Pada siklus II menunjukkan bahwa gerak dasar manipulatif meningkat hingga mencapai (80,55%). Penelitian ini menyimpulkan bahwa penerapan pendekatan teknis dapat meningkatkan gerak dasar manipulatif dalam pembelajaran field games sederhana.